2014
DOI: 10.1002/eji.201444731
|View full text |Cite
|
Sign up to set email alerts
|

IgE and IL‐33−mediated triggering of human basophils inhibits TLR4−induced monocyte activation

Abstract: Basophils are circulating granulocytes, best known as effector cells in allergic reactions.Recent studies in mice suggest that they might also participate in the suppression of chronic inflammation. The aim of this study was to assess the ability of purified human basophils to modulate monocyte responses upon IL-33 and IgE triggering. Activation of human basophils with IL-33 induced the production of IL-4 and the release of histamine, and enhanced their IgE-mediated activation. In addition, basophils triggered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…In vivo, IL-33 has been implicated in the ability of mast cells to contribute to the development of arthritis in murine experimental models (23,24), and high levels of IL-33 have been found in the serum and synovial fluid of patients with RA and those with other inflammatory arthritides (25). In addition to these proinflammatory properties, which are consistent with the described role of IL-33 as an alarmin, recent evidence suggests that this cytokine can also mediate immunoregulatory responses in various settings, by, for example, promoting regulatory T and B cell activity and suppressing monocyte activation through its effects on basophils (26)(27)(28)(29)(30)(31). Thus, similar to the findings regarding mast cells, the specific functions of IL-33 in the pathogenesis of autoimmune diseases, including arthritis, are still unclear (32,33).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…In vivo, IL-33 has been implicated in the ability of mast cells to contribute to the development of arthritis in murine experimental models (23,24), and high levels of IL-33 have been found in the serum and synovial fluid of patients with RA and those with other inflammatory arthritides (25). In addition to these proinflammatory properties, which are consistent with the described role of IL-33 as an alarmin, recent evidence suggests that this cytokine can also mediate immunoregulatory responses in various settings, by, for example, promoting regulatory T and B cell activity and suppressing monocyte activation through its effects on basophils (26)(27)(28)(29)(30)(31). Thus, similar to the findings regarding mast cells, the specific functions of IL-33 in the pathogenesis of autoimmune diseases, including arthritis, are still unclear (32,33).…”
mentioning
confidence: 68%
“…For blocking experiments, supernatants of activated mast cells were preincubated with anti–IL‐10 antibody or rat IgG2a as a matched isotype control (BD Biosciences), at 10 μg/ml for 30 minutes at 37°C in an atmosphere of 5% CO 2 , prior to being incubated with the monocytes. For inhibition of histamine, monocytes were preincubated for 30 minutes at 37°C with the histamine receptor 2 antagonist ranitidine (Sigma) at 10 −4 M .…”
Section: Methodsmentioning
confidence: 99%
“…These studies have shown increased degranulation and cytokine production when mast cells are exposed to combined triggers of e.g. IL-3, IL-4 and IL-33 with FcεRI crosslinking (Gebhardt et al, 2002;Lorentz et al, 2005;Ochi et al, 2000;Rivellese et al, 2014). Whereas these studies are important for understanding of the role of cytokines in allergic responses, Fcγ receptors, as compared to FcεRI, are probably more important for mast cell activation in rheumatoid arthritis.…”
Section: Chronic Inflammation Mediated By a Complex Interplay Of Multmentioning
confidence: 93%
“…Although the physiological role of mast cells and basophils remains enigmatic, there is now increasing evidence that these cells are critically involved not only in allergic disorders but also in autoimmune and infectious diseases, immunodeficiencies, and cancer [13,14,15,17,83], with multifaceted roles due to their ability to mediate both pro- and anti-inflammatory/immunomodulatory responses [21,23,84]. …”
Section: Differential Role Of Human Basophils and Mast Cells In Hiv Imentioning
confidence: 99%
“…However, there is now evidence that mast cells and basophils are versatile effector and regulatory cells able to initiate and modulate both innate and adaptive immune responses to parasites and bacterial pathogens [12,19,20]. Similarly, basophils and mast cells have been involved in many physiological and pathological processes, such as autoimmunity [21,22] and cancer [10], where they can play multifaceted roles with both pro- and anti-inflammatory/immunomodulatory functions [21,23]. The role of basophils and mast cells in viral infections is more enigmatic and has been less well studied [13].…”
Section: Introductionmentioning
confidence: 99%